2020
DOI: 10.26434/chemrxiv.12123204.v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In silico identification of widely used and well-tolerated drugs as potential SARS-CoV-2 3C-like protease and viral RNA-dependent RNA polymerase inhibitors for direct use in clinical trials

Abstract: <p></p><p>Despite strict measures taken by many countries, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continues to be an issue of global concern. Currently, there are no clinically proven pharmacotherapies for coronavirus disease 2019, despite promising initial results obtained from drugs such as azithromycin and hydroxyquinoline. Therefore, the repurposing of clinically approved drugs for use against SARS-CoV-2 has become a viable strategy. Here, we searched for drugs that … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 77 publications
(96 reference statements)
0
13
0
Order By: Relevance
“…No. Compound name Binding energy (kcal/mol) against SARS-CoV-2 proteins Mpro [24] (6Y84) PLpro [25] (6W9C) Spro [26] (6LZG) RdRp [27] (6M71) Helicase * [28] (6JYT/6ZSL) 1 Metacycline -9.1 2 Dutasteride -8.9 -9.9 # 3 Dihydroergotamine -8.6 -9.3 # 4 Nelfinavir -8.6 5 Tetracycline -8.1 6 Cryptophycin 1 -7.7 7 Cryptophycin 52 -8.3 ** -7.6 8 Deoxycylindrospermopsin -8.6 ** -7.9 9 Famotidine -6.0 ## -7.9 -6.8 ## -5.9 ## 10 Tegobuvir -8.1 11 Bromocriptin -7.7 12 Baicalin -7.6 13 Deleobuvir -7.6 14 Dantrolene -7.6 ...…”
Section: Resultsmentioning
confidence: 99%
“…No. Compound name Binding energy (kcal/mol) against SARS-CoV-2 proteins Mpro [24] (6Y84) PLpro [25] (6W9C) Spro [26] (6LZG) RdRp [27] (6M71) Helicase * [28] (6JYT/6ZSL) 1 Metacycline -9.1 2 Dutasteride -8.9 -9.9 # 3 Dihydroergotamine -8.6 -9.3 # 4 Nelfinavir -8.6 5 Tetracycline -8.1 6 Cryptophycin 1 -7.7 7 Cryptophycin 52 -8.3 ** -7.6 8 Deoxycylindrospermopsin -8.6 ** -7.9 9 Famotidine -6.0 ## -7.9 -6.8 ## -5.9 ## 10 Tegobuvir -8.1 11 Bromocriptin -7.7 12 Baicalin -7.6 13 Deleobuvir -7.6 14 Dantrolene -7.6 ...…”
Section: Resultsmentioning
confidence: 99%
“…A To discover an antiviral drug diverse targets are available from viral replication enzymes to host proteins facilitating the virus entry and to proteins responsible for the virus release (Boopathi et al, 2020;Lo et al, 2020;Wu C and Zheng M, 2020). Several in silico and in vivo drug repurposing studies are carried out using proteases (3CL pro and PL pro ) and RNA-dependent RNA polymerase (RdRp) of SARS-CoV-2 as targets (Bharadwaj et al, 2020;Ghosh et al, 2020;Gul et al, 2020;Li et al, 2020c;Wang, 2020). In addition, host proteins TMPRSS2 and ACE2 which primes protein S and mediates SARS-CoV-2 entry to host, respectively, are targeted for drug repositioning as well (Bagheri and Niavarani, 2020;Busnadiego et al, 2020;Carino et al, 2020;Choudhary et al, 2020;Durdagi, 2020;Kumar et al, 2020;Singh et al, 2020b).…”
Section: Resultsmentioning
confidence: 99%
“…During the MD simulations interacting residues of EG01377 and eltrombopag with NRP1 are very similar to each other ( Figure 4B). A previous drug-repurposing study against 3CL pro and RdRp of SARS-CoV-2 from our group showed that eltrombopag may bind to the active site of 3CL pro and nsp8 binding site of RdRp which may attenuate the virus activity (Gul et al, 2020). Eltrombopag exhibits in vitro antiviral properties with IC50 lower than 10µM (Jeon et al, 2020).…”
Section: Simulations and Binding Free Energy Calculationmentioning
confidence: 87%
See 2 more Smart Citations